Improved Chicken Reproduction and Yield of Improved Poultry from Titanium Dioxide (TiO2) Nanoparticles Coated in Jimma Horro Area of Kellem Wollega Zone, Ethiopia - Soressa Shuma Abdisa; Jule Leta Tesfaye; Abel Saka; Abdisa Abraham; N. Nagaprasad; Lamessa Gudata; Krishnaraj Ramaswamy (Advances in Materials Science and Engineering)
Current work was accompanied in Kellem Wollega Zones Jima Horro District, Western Ethiopia, to evaluate the reproduction and productive performances of titanium dioxide (TiO2) nanoparticles’ coated poultry. In the existence of sunlight as well as moistness, the titanium dioxide rusts and abolishes microorganisms (bacteria). The covering has been confirmed to decrease bacterial development. Once covered, the superficial remainders self-sanitized as it elongated as there is sufficient sunlight to galvanize the photocatalytic outcome. The middling poultry group scope per family was 12.04 heads. The overall middling time at first of local and improved chicken egg laying was 6.9 and six months, respectively. The overall hatchability and mortality were 82.3 and 41.1, respectively. The lowest chick mortality (39.8) was observed in Tribe Kebele (highland), and the highest clutches per year (2.96) were observed compared to other Kebeles (mid-altitude and low land). Poultry reproductivity is little, so diverse development approaches must be familiarized. The application of TiO2 nanoparticles in agriculture is a promising method in increasing fine and improved products.